A Cause of Asthma Misdiagnosis: Foreign Body Aspiration That Allows Air Passage Through - Zeynep Reyhan Onay; Yetkin Ayhan; Nilay Bas Ikizoglu; Ersan Uzun; Gülay Bilgin; Saniye Girit (Galenos Publishing House, 2021)
Foreign body aspiration is a life-threatening condition in childhood. Clinical and radiological diagnosis may be delayed in cases in which foreign body has a lumen and allows the air passage through and is also misdiagnosed as asthma or chronic cough. The delay in the diagnosis can cause morbidity and mortality. We have reported the case of an 11-year-old boy with foreign body aspiration who has been treated as asthma. His dry cough could not be controlled with the asthma treatment. He had swallowed a piece of pipette before the coughing started. Fiber optic bronchoscopy was applied. The piece of pipette was seen in the left main bronchus which allowed the air passage through its lumen. After the removal, his complaints disappeared. In conclusion, the patients with a history of aspiration and without signs of lateralization in physical or radiological examinations should be evaluated by fiber optic bronchoscopy in terms of foreign body aspiration.